Employee Performance Analysis of the Population and Civil Registration Office in Bengkulu City in the "3 in 1 Duka Cita" Service - Anggara, Rema; Lorita, Evi; Rikardo, Yanuar (Social Sciences Journal, 2025)
Findings indicate that while the implementation of the "3 in 1 Duka Cita" service has generally been effective in easing administrative burdens for grieving families, several obstacles remain. These include limited human resources, coordination challenges across departments, and inconsistent communication to the public. Despite these challenges, the dedication of front-line staff and simplified service mechanisms contribute significantly to service success. The research also reveals that employee performance is influenced by internal motivation, availability of resources, and clear job descriptions. The study concludes that while the initiative aligns with public service improvement goals, continuous monitoring, capacity building, and public education are needed to enhance overall performance and sustainability. This research contributes to understanding how integrated services in civil registration can be optimized through focused performance evaluation and organizational improvements.